Emerging design principles for environmental, economic, and equity successes in land conservation - Katharine R. E. Sims; Jennifer M. Alix-Garcia (Proceedings of the National Academy of Sciences, 2026)
Land conservation initiatives worldwide are poised to continue rapid growth. Ranging in scale, scope, and mechanisms, these efforts include area-based conservation, incentive-based protection, and community collective management. Evidence from across fields now indicates that it is possible for land conservation to jointly improve environmental conditions, generate positive net local economic benefits, and support social equity. Yet the key policy elements that can lead to this type of multidimensional success are not well understood. Here, we review the considerable body of existing research on land conservation and propose eight emerging design principles that conservation actors can employ to support “win-win-win” outcomes: 1) identify and support credible pathways of change, 2) set goals for all outcomes, recognizing their interdependencies, 3) accommodate multiple needs and uses through spatial or place-specific differentiation, 4) facilitate temporal resilience through diversification and limits, 5) foster nested governance, 6) integrate information structures for environmental and social outcomes, 7) assess policies using counterfactual-based analysis and adaptive management, 8) establish lasting institutions and funding mechanisms. Although these design principles will likely change and evolve, they provide an evidence-grounded framework to support current and future efforts to steward global lands.